The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1589/jpts.17.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Physiotherapy: A Study of Ishikawa High School Students

Abstract: Abstract. OBJECTIVE: To investigate how senior high school students' knowledge of physiotherapy is acquired and their possible view of physiotherapy as a career. DESIGN: Cross-sectional survey. SETTING: Two non-vocational senior high schools in Japan. PARTICIPANTS: Six hundred and twentythree students with a scholastic deviation value of more than 60. METHODOLOGY: A questionnaire in a closed-question format was used to survey the students' accuracy of knowledge and sources of information about physiotherapy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
(6 reference statements)
3
13
0
Order By: Relevance
“…There is little other previous research exploring public understanding of physiotherapy and none pertaining to FPCP. Evidence derived from high school age students was consistent with this research in that understanding of the clinical application of physiotherapy practice is poor [27,28].…”
Section: Discussionsupporting
confidence: 58%
“…There is little other previous research exploring public understanding of physiotherapy and none pertaining to FPCP. Evidence derived from high school age students was consistent with this research in that understanding of the clinical application of physiotherapy practice is poor [27,28].…”
Section: Discussionsupporting
confidence: 58%
“…This was comparable to the results obtained by Ogiwara et al (7) in Japan and Kallus et al (6) for the USA. In both studies, approximately half of their respondents also incorrectly identified "prescribing medications" as a task fulfilled by physical therapists.…”
Section: Discussionsupporting
confidence: 91%
“…The same instrument used in the USA was utilized in two non-vocational senior high schools in Ishikawa, Japan (7). The mean number of correct items on the knowledge section was found to be lower than that obtained in the USA (4.3 ± 3.3).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is also noticed that student assumes masseurs are Physiotherapist, But the fact is Physiotherapist practice massage as a part of their treatment technique on the other hand all masseurs are not Physiotherapist. When we compare with similar studies done by Shimpachiro [3] in japan among ishikawa high school students it was noted 58% of respondents were believed to have had some knowledge in Physiotherapy. Whereas in the study conducted in high school students in Sri Lanka more than 63% of them were unaware about physiotherapy profession & its applications in patient management [4].…”
Section: Discussionmentioning
confidence: 57%